EFL Learners’ Perspectives on AI-Produced and Instructor Feedback in Improving Second Language Writing - Alshahrani, Abdulaziz; Al-Inbari, Fatima Abdullah Yahya (Journal of Posthumanism, 2025)
Students learning English as a foreign language frequently encounter difficulties with organization, content quality, linguistic precision, and objectivity. Teacher feedback has traditionally served as a means to address these challenges. Nevertheless, instructors managing large classes face constraints related to workload and available time for reviewing student compositions. These limitations hinder the provision of effective feedback. Feedback systems powered by Artificial Intelligence (AI) offer potential solutions to some of these complex challenges, providing benefits such as scalability, rapid response times, and objectivity. However, AI-based feedback systems may struggle to comprehend individual learner requirements and occasionally deliver inaccurate or problematic guidance. Consequently, both teacher-provided and AI-generated feedback present distinct advantages and limitations. The purpose of this study was to examine and compare Saudi EFL students’ perceptions regarding teacher feedback and AI feedback in the context of improving L2 writing competence. A mixed-methods research design was utilized to investigate how English as a Foreign Language (EFL) students perceive AI-generated feedback in comparison with teacher feedback concerning their L2 writing development. The research integrated quantitative survey data with qualitative interview responses to develop a comprehensive understanding of student preferences and perspectives toward various feedback sources. The survey component recruited 50 undergraduate students enrolled in English language courses at a large public university in Saudi Arabia. From this group, 15 students were selected for in-depth interviews. Statistical methods were applied to analyze quantitative data, while thematic analysis was employed for qualitative data. The findings and discussion sections of this study support the conclusion that AI feedback and teacher feedback offer distinct advantages for enhancing EFL students’ L2 writing competence. A complementary relationship exists between these two feedback approaches in addressing students’ concerns regarding their L2 writing development. Accordingly, an integrated hybrid methodology that thoughtfully combines both feedback types can prove beneficial for addressing the majority of student concerns related to L2 writing proficiency.